Indonesian stock market: Do bear and bull matter? - Wisnu wibowo, Rossanto Dwi Handoyo, Mohd. Azlan Shah Zaidi, (Opción, 2020)
In this paper we attempt to investigate the foreign shock and domestic shock on determining the period of the bull and the bear of Indonesian Stock market. In particular, we investigate the impact of oil market, global stock market, money market, exchange rate market, and output market as explanatory variables in determining the period of bear and bull of stock market. The markets that perform well to predict the period of bull and bear period of Indonesian Stock Market are world oil market, Malaysia Stock Market, Singapore Stock Market, US Stock market and foreign exchange market.